Witnessing well-being in action: Observing teacher well-being during field experiences predicts student teacher well-being - Dreer, Benjamin (Frontiers in Education, 2023)
Social cognitive theory posits that observing others’ behavior can influence our thinking, behavior, and learning. The present study examines whether this principle also applies to teacher well-being. It investigates whether student teachers’ well-being is linked to the well-being of in-service teachers they closely observe during field experiences. For that purpose, student teachers were assigned to conduct three classroom observations of three different teachers using a dedicated observation tool that focused on in-service teachers’ positive emotions and positive student interactions. Longitudinal data from 159 classroom observations and student teachers’ well-being data were analyzed. It was hypothesized that the mean scores from all three independent classroom observations are most predictive of student teacher well-being. The results revealed significant associations between six of seven indicators of student teacher well-being and the observed well-being of in-service teachers. Interestingly, it was not the mean of all three observation scores but only the score of the third and final observation that contributed significantly to student teacher well-being. This brief research report seeks to inspire discourse about the benefits and challenges of observational learning in teachers’ well-being education.